An Analysis of Pronouncing English Phonemes on the Fifth-Semester at Lakidende University - Fadli, M. (Indonesian Research Journal on Education, 2025)
Pronouncing English words that having vowel & consonant sounds properly seems to be a challenge for Indonesian students. This research aims to analyze and describe the pronunciation of English sounds made by the 5th semester students of the English Education Department at Lakidende University and find out what factors might be the influence of the pronunciation errors of English sounds that they often do. This research used a qualitative approach with an error analysis method. Data was collected through observation, interview, and documentation. The data collected in this research is in the form of transcription of students’ English speech and in the form of text from interview. The data analysis technique was carried out based on the theory of Carl James (identification, description & classification). The most frequent errors found in vowel sounds are short vowel [ᴂ] and long vowels [3:] & [ɑ:]. While the most frequent errors in consonant sounds are voiced consonants [ð] & [ʒ] and voiceless consonant [θ]. Then, there are 4 influencing factors of their pronunciation errors, namely: the influence of the mother tongue, the environment, unfamiliar words, and the ineffectiveness of the teaching process. Therefore, the researcher suggests that both for students itself or English lecturers can be paid more attention to the correct pronunciation as a prospective English teacher in the future.